2017
DOI: 10.1192/bjp.bp.116.189993
|View full text |Cite
|
Sign up to set email alerts
|

Predictive accuracy of risk scales following self-harm: Multicentre, prospective cohort study

Abstract: BackgroundScales are widely used in psychiatric assessments following self-harm. Robust evidence for their diagnostic use is lacking.AimsTo evaluate the performance of risk scales (Manchester Self-Harm Rule, ReACT Self-Harm Rule, SAD PERSONS scale, Modified SAD PERSONS scale, Barratt Impulsiveness Scale); and patient and clinician estimates of risk in identifying patients who repeat self-harm within 6 months.MethodA multisite prospective cohort study was conducted of adults aged 18 years and over referred to l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
82
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 105 publications
(94 citation statements)
references
References 60 publications
3
82
0
Order By: Relevance
“…Organizational processes reported in the current study focussed on paternalistic, formulaic approaches to risk, serving organizational accountability agendas related to the origination of care planning as a result of concerns about safety and fragmented community care . The findings support the recent literature demonstrating that actuarial risk assessments can be used by professionals to manage uncertainty in a manner that distances service users from potential solutions . To better integrate care plans with people's everyday lives, risk management should be separated from holistic needs elicitation.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Organizational processes reported in the current study focussed on paternalistic, formulaic approaches to risk, serving organizational accountability agendas related to the origination of care planning as a result of concerns about safety and fragmented community care . The findings support the recent literature demonstrating that actuarial risk assessments can be used by professionals to manage uncertainty in a manner that distances service users from potential solutions . To better integrate care plans with people's everyday lives, risk management should be separated from holistic needs elicitation.…”
Section: Discussionsupporting
confidence: 66%
“…12 The findings support the recent literature demonstrating that actuarial risk assessments can be used by professionals to manage uncertainty in a manner that distances service users from potential solutions. [33][34][35] To better integrate care plans with people's everyday lives, risk management should be separated from holistic needs elicitation. The latter could be elicited through tailored dialogue between service users and professionals with the former developed separately through formulaic and less engaging processes.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical data used to populate the model were obtained from a prospective cohort study evaluating 12 risk scales following hospital-treated self-harm in five hospitals in England. Full details of the study are 13 reported elsewhere (Quinlivan et al, 2017). In short, that study involved 514 patients aged 18 years 14 and over who were referred to liaison psychiatry service following self-harm and consented to take 15 part in a multi-site prospective cohort study evaluating the predictive accuracy of risk scales following 16 self-harm between March 2014 and January 2015.…”
Section: Clinical Inputs 11mentioning
confidence: 99%
“…The assessment scales used in the study were selected on the basis of a systematic review of the 22 diagnostic accuracy of risk scales following self-harm (Quinlivan et al, 2014b) and a cohort study of 23 their diagnostic accuracy (Quinlivan et al, 2017). Clinician and patient global ratings of risk of repeated 24 self-harm within six months (using a 1-10 Likert-type scale) were also included.…”
Section: Clinical Inputs 11mentioning
confidence: 99%
See 1 more Smart Citation